Perception of RNA Nanotechnology Among Students and Recommendations Towards Improved Educational Outreach - Kozlov, Seraphim (Archives of Clinical and Biomedical Research, 2022)
Translating new technologies to industrial and biomedical applications requires a highly skilled workforce. In the past, colleges and graduate schools played a primary role in preparing students for various areas of industry and medicine. The learning process and introduction of new concepts have recently extended beyond college education. High schools saw the rise of specialized career programs, while both high and middle school curricula got infused with challenging concepts. Nucleic acids, such as DNA and RNA, are broadly known for their role in the foundation of life. However, nucleic acid nanotechnology, an area of material science manipulating DNA and RNA to create complex structures with controlled properties, is less known. Herein, I report the results of a study investigating the perception of RNA nanotechnology among school students and suggest educational resources to improve understanding of RNA nanotechnology.